2001
DOI: 10.1002/app.1360
|View full text |Cite
|
Sign up to set email alerts
|

Modification of bismaleimide with allyl compound and N‐phenylmaleimide

Abstract: Three different formulas with low-cost resins, made up of N,NЈ-bismaleimidephenylmethane (BMI), O,OЈ-diallybisphenol A(BA), and N-phenylmaleimide (NPMI) were developed. The properties of prepolymers, such as activation energies, enthalpy, and constants of reaction rate, were obtained by a kinetic programmer on DSC. Thermal and mechanical properties of neat resins were also studied. The results showed that the systems had low melting point and low viscosity. All cured resins presented excellent thermal and good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For example, Xiaoyan et al studied the degradation of melt-spun PLLA fibers in a phosphate-buffered solution (PBS) with a pH of 7.4 at 37 C. They found a substantial decrease in the molecular weight of PLLA, a minor decrease in tensile strength, and almost no change in the mass loss after 35 weeks. In addition, microcracks perpendicular to the fiber direction appeared after 45 weeks of degradation, indicating a decrease in the molecular weight of the PLLA fibers [4]. Joziasse et al reported that a 25% loss in the mechanical properties of a dry-spun PLLA fiber can be observed after 5 years of degradation in PBS at room temperature under tension [5].…”
Section: Introductionmentioning
confidence: 97%
“…For example, Xiaoyan et al studied the degradation of melt-spun PLLA fibers in a phosphate-buffered solution (PBS) with a pH of 7.4 at 37 C. They found a substantial decrease in the molecular weight of PLLA, a minor decrease in tensile strength, and almost no change in the mass loss after 35 weeks. In addition, microcracks perpendicular to the fiber direction appeared after 45 weeks of degradation, indicating a decrease in the molecular weight of the PLLA fibers [4]. Joziasse et al reported that a 25% loss in the mechanical properties of a dry-spun PLLA fiber can be observed after 5 years of degradation in PBS at room temperature under tension [5].…”
Section: Introductionmentioning
confidence: 97%
“…In order to increase two phase contact, PCl 5 and NH 4 Cl may be put in inert solvent which has commonly tetrachloroethane, chlorobenzene, pyridine and so on, heated and reflux. When the molar ratio of PCl 5 and NH 4 Cl is controlled in 1:1.1 to 1:1.3, product yield can be increased to 70.3~87% [6,7,8]. There are still n=4~7 annular crystal and n=8~15 oily matter in addition to n=3 main products in coarse products which can be purified by recrystallizing with normal hexane.…”
Section: The Synthesis Methods Of the Hexachlorocyclotriphosphazenementioning
confidence: 99%